Synthesis of Cyclic Imides from Simple Diols - Zhang, Jian; Senthilkumar, Muthaiah; Ghosh, Subhash Chandra; Hong, Soon Hyeok (Angewandte Chemie (International ed.), 2010)
There′s something imide so strong: Cyclic imides were synthesized from simple diols with primary amines in a single step using an in‐situ‐generated ruthenium catalytic system. The atom‐economical and operatively simple syntheses of succinimides, phthalimides, and glutarimides, which are important building blocks in natural products and drugs, was also demonstrated.